Clinical features of early-onset type 2 diabetes and its association with triglyceride glucose-body mass index: a cross-sectional study - Jiang, Yanjuan; Lai, Xiaoyang (Frontiers in Endocrinology, 2024)
Objective: The incidence of early-onset type 2 diabetes (T2D) has increased significantly, with insulin resistance (IR) and obesity being the main drivers of its onset. This study aims to investigate the clinical characteristics of early-onset T2D and its association with triglyceride glucose body mass index (TyG-BMI), an emerging surrogate of IR.Methods: A total of 1000 adults newly diagnosed with T2D were enrolled and divided into early-onset T2D (18 ～ 40 years, N=500) and late-onset T2D groups (≥40 years, N=500).Independent t and chi-squared tests were used to compare the characteristics of the two groups, and logistic regression analysis, trend tests, restricted cubic spline curves (RCSs), and receiver operating characteristic (ROC) curves were used to identify the relationship between TyG-BMI and early-onset T2D.Results: Patients with early-onset T2D were more likely to have a higher body mass index (BMI), hemoglobin A1C (HbA1c), fasting plasma glucose (FPG), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), serum uric acid (SUA), triglyceride glucose index (TyG), and TyG-BMI (P < 0.05). A higher TyG-BMI was associated with an increased risk of early-onset T2D (P < 0.001). The RCSs showed a nonlinear relationship between TyG-BMI and early-onset T2D, and the slope of the curve increased with an increase in TyG-BMI (P for nonlinearity < 0.001). In the subgroup analysis, additive interactions between TyG-BMI and the risk of early-onset T2D were observed for sex, family history of diabetes, BMI, fatty liver, and hypertension (P < 0.001). ROC curve showed that the area under the curve of TyG-BMI was 0.6781, which was larger than its main components (TyG, BMI, FPG, TG). The best cutoff value was 254.865, the sensitivity was 74.6 %, and the specificity was 53.6%.Conclusion:Patients with early-onset T2D are characterized by severe IR, metabolic disorders, and being overweight/obese and an increase in TyG-BMI is independently associated with an increased risk of early-onset T2D.